Large Spin Hall Efficiency and Current‐Induced Magnetization Switching in Ferromagnetic Heusler Alloy Co2MnAl‐Based Magnetic Trilayers - Mingzhi Wang; Chang Pan; Nian Xie; Xuepeng Qiu; Yufei Li; Lili Lang; Shiqiang Wang; Dashuai Cheng; Weijia Fan; Shi‐Ming Zhou; Zhong Shi (Advanced Science)
Abstract The spin Hall efficiency (ξ) is a crucial parameter that evaluates the charge‐to‐spin conversion capability of a material, and thus materials with higher ξ are highly desirable in spin–orbit torque (SOT) devices. Recent studies have highlighted the use of ferromagnetic materials as robust spin sources, paving the way for the development of more efficient SOT devices. To accelerate this innovation, it is essential to pursue ferromagnetic materials of high ξ. Here the experimental observation of a large spin Hall efficiency is reported in ferromagnetic Heusler alloy Co2MnAl (CMA)‐based magnetic trilayers. Utilizing the current‐induced hysteresis loop shift technique, the spin Hall efficiency is determined to be 0.077 for the B2‐phase and 0.029 for the disordered CMA. Notably, magnetization switching both with and without the application of an external auxiliary magnetic field were achieved in these trilayers. The enhancement of ξ is attributed to the formation of chemical ordering in CMA. These findings provide new avenues for the development of ferromagnet‐based SOT devices.